Salicylanilides and Their Anticancer Properties - Kauerová, Tereza; Pérez-Pérez, María-Jesús; Kollar, Peter (International journal of molecular sciences, 2023)
Salicylanilides are pharmacologically active compounds with a wide spectrum of biological effects. Halogenated salicylanilides, which have been used for decades in human and veterinary medicine as anthelmintics, have recently emerged as candidates for drug repurposing in oncology. The most prominent example of salicylanilide anthelmintic, that is intensively studied for its potential anticancer properties, is niclosamide. Nevertheless, recent studies have discovered extensive anticancer potential in a number of other salicylanilides. This potential of their anticancer action is mediated most likely by diverse mechanisms of action such as uncoupling of oxidative phosphorylation, inhibition of protein tyrosine kinase epidermal growth factor receptor, modulation of different signaling pathways as Wnt/β-catenin, mTORC1, STAT3, NF-κB and Notch signaling pathways or induction of B-Raf V600E inhibition. Here we provide a comprehensive overview of the current knowledge about the proposed mechanisms of action of anticancer activity of salicylanilides based on preclinical in vitro and in vivo studies, or structural requirements for such an activity.
Keywords: Niclosamide; Signal Transduction; salicylanilidy; lidé; Anthelmintics; Salicylanilides; signální transdukce; anthelmintika; niklosamid; Humans